Mathematical modeling of priorities and costs of Vernadsky station infrastructure modernisation - O. V. Kuzko; V. D. Lukiashchenko; M. A. Leonov (Ukrainian Antarctic Journal, 2017)
Objective. The topical issue of Ukrainian Antarctic Akademik Vernadsky Station infrastructure system modernization was investigated to prevent accidents and failures of the infrastructure constituent elements, to Antarctica environmental conservation, and to carrying out of Ukraine’ international obligations in Antarctica. Methods. The Antarctic Treaty Consultative Meeting (ATCM-XXXIII) adopted Resolution 3 (2010) with the Check List A to verify by the international inspections, particularly, the technical conditions of Antarctic stations infrastructures. The authors used both this Check List A and the mathematical modelling of the hierarchies study (Saaty, 2008) to obtain the quantitative characteristics of priorities and costs of Vernadsky station infrastructure modernization. Mathematical modelling was done in three stages: preparing of the two matrices (for priorities and costs) with the list of the station infrastructure elements; filling the matrices by expert estimates of successive pairwise comparison of importance (priorities and costs) of infrastructure each elements according to ranks from 0 to 9 (subject to conditions, particularly, if aij = 1, then aji = 1/aij); eigenvalues calculating of obtained matrices which after the normalization procedures gave the necessary quantitative characteristics. Results. Quantitative results on the priorities and cost of Vernadsky station infrastructure modernization were obtained. Conclusions. The obtained results will be used to the feasibility study justification of the station infrastructure modernization, to the argumentation and decision-making by the executive authorities of Ukraine, to inform the general public of Ukraine. In addition, the obtained results will contribute to the further development and implementation of other approaches to assessing the priorities and costs of Vernadsky station infrastructure modernization.